Craniopharyngioma involving the anterior, middle, and posterior cranial fossa in adults: A case report - Tian, Bin; Li, Ming; Du, Xiaolin; Zhou, Hui; Zhou, Kun; Li, Shiguang (Frontiers in Neurology, 2023)
Craniopharyngioma (CP) is a rare benign tumor that develops from the residual epithelial cells of the craniopharynx, accounting for < 5% of intracranial tumors. It is common for CPs to grow in the sellar/parasellar region and extend suprasellar. The pathology classifies CPs into adamantinomatous craniopharyngiomas (ACP) and papillary craniopharyngiomas (PCP). The PCP is mainly solid and occurs only in adults. ACP is predominantly cystic and more common in childhood and adolescent. Multilocular cystic ACP involving the anterior, middle, and posterior cranial fossa is rare in adults. Here, we report a case of a 46-year-old adult male patient who presented with recurrent headaches for 1 year with choking and hoarseness. Computed tomography (CT) and magnetic resonance imaging (MRI) revealed multiple cystic masses in the anterior, middle, and posterior cranial fossa. Initial hypotheses included the following: CP, colloid cyst, enterogenous cyst, epidermoid cyst, and dermoid cyst. Subsequently, the patient underwent surgery and postoperative histopathology diagnosed ACP. Adults with ACP involving the anterior, middle, and posterior cranial fossae are uncommon. This is a rare condition that radiologists should be aware of.